Reflections on student-centered learning: An alternative to traditional English classes - Fonseca Cely, Sulma Patricia; Cano García, Leidy Girleza (Universidad Pedagógica y Tecnológica de Colombia, 2018)
This article presents some methodological reflections about student-centered learning in order to achieve the Colombian National Standards for Bilingual Education in English classes in an elementary school context. It also discusses the need to raise teacher awareness, understanding of these methodologies, and the need to change teachers´ beliefs and behaviors in the classroom. Findings show that student-centered learning is an alternative for teachers, and it should be included in schools’ Proyecto Educativo Institucional (PEI) in order to achieve bilingualism. Furthermore, it allows students to explore, practice and increase their autonomy and self-confidence in using a foreign language.